After-effects of pedaling exercise on spinal excitability and spinal reciprocal inhibition in patients with chronic stroke. (2nd January 2017) - Tanuma, Akira; Fujiwara, Toshiyuki; Yamaguchi, Tomofumi; Ro, Takanori; Arano, Hirotaka; Uehara, Shintaro; Honaga, Kaoru; Mukaino, Masahiko; Kimura, Akio; Liu, Meigen
Abstract : Purpose of the study : To evaluate the after-effects of pedaling on spinal excitability and spinal reciprocal inhibition in patients with post-stroke spastic hemiparesis. Materials and methods : Twenty stroke patients with severe hemiparesis participated in this study and were instructed to perform 7 min of active pedaling and 7 min of passive pedaling with a recumbent ergometer at a comfortable speed. H reflexes and M waves of paretic soleus muscles were recorded at rest before, immediately after and 30 min after active and passive pedaling. The Hmax/Mmax ratio and H recruitment curve were measured. Reciprocal inhibition was assessed using the soleus H reflex conditioning test paradigm. Results : The Hmax/Mmax ratio was significantly decreased after active and passive pedaling exercise. The decreased Hmax/Mmax ratio after active pedaling lasted at least for 30 min. The H recruitment curve and reciprocal inhibition did not change significantly after active or passive pedaling exercise. Conclusions : Pedaling exercise decreased spinal excitability in patients with severe hemiparesis. Pedaling may be effective in rehabilitation following stroke.